Direct measurement of stool consistency by texture analyzer and calculation of reference value in Belgian general population - Kazunori Matsuda; Takuya Akiyama; Satoshi Tsujibe; Kaihei Oki; Agata Gawad; Junji Fujimoto (Scientific Reports, 2021)
Abstract Stool consistency is evaluated mainly in reference to indirect indicators such as water content or the appearance of stool forms using Bristol Stool Form Scale (BSFS). Methods of measurement are limited. We thus aimed to develop a simple protocol for direct measurement of stool consistency using the TA.XTExpress Texture Analyser (Stable Micro Systems Ltd.). We developed a protocol which enables mechanical quantification of the gram-force against a cylindrical probe (ø 6 mm) pushed into the stool surface at 2.0 mm/s to 5 mm depth. The consistency of 252 stools collected from 40 healthy Belgians was evaluated by the direct method and by the indirect indicators (water content and BSFS) for comparison. The log-transformed stool consistency values measured by the texture analyzer had a negative linear correlation with the stool water contents (r rm  = − 0.781) with homoscedastic variance, suggesting the appropriateness of the new protocol. They showed a similar correlation with the BSFS, but with a large variance in the consistency values of normal stool forms. This correlation was much smaller for BSFS scored by subjects (r rm  = − 0.587) than by experts (r rm  = − 0.789), collectively indicating BSFS as a rough indicator of stool consistency susceptible to subjective bias despite its effectiveness in clinical use. The optimized direct method using the texture analyzer enables the accurate quantification of stool consistency, which facilitates understanding of the intestinal environment and function and thus may enhance the value of the stool as a predictor of human health.